Attributions regarding acquaintance rape: stage of relationship, alcohol use, and a methodological consideration - Lovell, Rhonda S. (1995)
This study examined lay attributions regarding situations meeting the legal definition of rape and in addition examined a methodological question regarding the effect of use of a projective measure upon participant involvement and lay attributions. Eight scenarios completely crossed three two-level factors: stage of relationship, and victim and perpetrator alcohol consumption. The stage of relationship variable partially operationalized Shotland's (1989, 1992) courtship rape theory, which posits that acquaintance rape is not a unitary phenomenon. Half of the participants were asked to complete a projective section requesting that they complete sentence blanks regarding the inner cognitions and feelings of the rapist. All participants then responded to the Acquaintance Rape Attributions Questionnaire (ARAQ), which elicited information regarding the rapist's motivations and intentions. Results suggested that participants perceive beginning courtship rape and relational courtship rape differently, ascribing a stronger intent to rape and power motivation to the rapist who has known his victim for a relatively short amount of time (beginning courtship rape). In cases of relational courtship rape, participants were more likely to apply sexual interaction scripts (i.e., a man is entitled to sex if a woman leads him on and a woman may play hard to get but will eventually relax and enjoy herself). Male participants and participants holding rape supportive attitudes were more likely to invoke such sexual scripts. Participants who completed the projective measure were more likely to view the incident as resulting from sexual miscommunication that the victim should have prevented, and they expressed a lower level of involvement in the task